(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores phonolistics, a proposed interdisciplinary approach that synthesizes phonetics, phonology, and other linguistic subfields to study the role of sounds in language. It begins by defining phonolistics as an integrated framework, highlighting its focus on the intersection of physical sound properties, systemic sound patterns, and their interaction with linguistic and social contexts. The